KEHIDUPAN SOSIAL MASYARAKAT BAURAN: ANALISIS PADA INTERKASI KELOMPOK ETNIS TIONGHOA DENGAN MASYARAKAT LOKAL - Riska Mutiah (KOMUNITAS, 2021)
The interaction between ethnic groups in a social sphere is always related to integration issues. Moreover, the Indonesian people are diverse with their inherent cultural identities. The pattern of interaction between the Chinese and several local ethnic groups in Indonesia has been investigated by various parties, including in Medan, Bengkalis, and Yogyakarta. The results of the three studies show that the interaction between these groups only occurs in the economic realm. It causes the inability to merge in the assimilation process. The author wants to examine why the pattern of interaction between ethnic Chinese and local communities does not reach the point of assimilation by using literature study as methodology. The analysis shows that the relationship among them is not in close proximity but more at public distance. Such a distance happened because the relationship patterns between these groups are fragmented then induces the emergence of organic solidarity among them.